2012
DOI: 10.1590/s0102-695x2011005000211
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical, pharmacognostical, pharmacological and phytochemical studies on Smilax domingensis in Guatemala

Abstract: Smilax domingensis Willd., Smilacaceae, known as zarzaparrilla, is a climbing shrub from Tropical America. The rhizome is popularly used in medicine as anti-infl ammatory, antiseptic, and tonic. Since 1983 studies are being conducted in Guatemala for validation of the ethnobotanical uses, particularly in vitro demonstration of antimicrobial activity, using wild material, with high variability and some taxonomic problems. This article reports the taxonomic determination, cultivation of drug material, evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…It is evident that the analyzed spice has a great coincidence by the description done by Ferrufino & Gómez-Laurito [11], and Cáceres [12]. We finally arrived to a clear description of S. domingensis in Cuba, represented by a big woody red rhizome.…”
Section: Phytochemical Studiessupporting
confidence: 60%
See 1 more Smart Citation
“…It is evident that the analyzed spice has a great coincidence by the description done by Ferrufino & Gómez-Laurito [11], and Cáceres [12]. We finally arrived to a clear description of S. domingensis in Cuba, represented by a big woody red rhizome.…”
Section: Phytochemical Studiessupporting
confidence: 60%
“…From 10 samples from different locations in Guatemala, chromatographic profiles were similar, with the exception of a sample from Carchá, which showed fragmentation patterns similar to sarsapogenin/smilagenin, which correspond to Smilax kunthii [12].…”
Section: Phytochemical Studiesmentioning
confidence: 90%
“…The same authors confirmed the presence of saponins by the stirring test and the verification of persistent foam. In the present study, Rf of 0.8 was not detected because we didn't obtain satisfactory results using the same mobile phase of Cáceres et al (2012).…”
Section: Chemical Profilementioning
confidence: 57%
“…According to Cáceres et al (2012), steroidal saponins are the main component of medicinal properties attributed to Smilax extracts. The authors report the presence of saponins in the ethanol extract of Smilax domingensis Willd.…”
Section: Chemical Profilementioning
confidence: 99%
“…After a 12-hour fasting period, four groups of six to eight rats each were orally treated with SLG (100, 200, or 400 mg/Kg) or vehicle (1% Teen 80, equivalent volume). These doses were chosen based on previous in vivo studies using extracts from other species of Smilax [5, 19]. One hour after the SLG or vehicle treatment, edema was induced by intraplantar injection of carrageenan (Cg; 200  μ g/paw; in 0.1 mL of saline).…”
Section: Methodsmentioning
confidence: 99%